Architectural approaches to build the Museum of the Person - Araújo, Cristiana (2016)
The Museum of the Person (Museu da Pessoa, MP) is a virtual museum aimed at exhibiting life stories of common people. Its assets are composed of several interviews involving people whose stories we want to perpetuate. So the museum holds an heterogeneous collection of XML (eXtensible Markup Language) documents that constitute the working repository. The main idea is to extract automatically the information included in the repository in order to build the web pages that realize the museum's exhibition rooms. This project started by creating a specific ontology (OntoMP) for the knowledge repository of MP. That ontology is intended to allow a conceptual navigation over the available information. We will adopt the standard for museum ontologies CIDOC-CRM (CIDOC Conceptual Reference Model) refined with FOAF to represent OntoMP. The objective of this paper is to discuss different architectural approaches to build a system that will create the virtual rooms from the XML repository to enable visitors to lookup individual life stories and also intercross information among them. The first architecture is based on a TripleStore and uses SPARQL (SPARQL Protocol and RDF Query Language) technology to extract the information, while the second proposal is based on a Relational Database and uses CaVa Generator to query the repository and build the exhibition spaces.